THE INFLUENCE OF MAGNITUDE AND NUMBER OF FLOOD CASES FOR UNIT HYDROGRAPH CALCULATION TO DESIGNED DISCHARGE ACCURATENESS - Revianti Coenraad (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
Various methods can be used to predict design discharge, such as unit hydrograph theory. Problem to be coped with is the number of flood case required to derive the unit hydrograph for obtaining a unit hydrograph that represents a watershed and to obtain accurateness of certain design discharge. Subject of this study is based on four watersheds, two in the Province of Daerah Istimewa Yogyakarta: Code and Gajahwong watersheds, and two in the Province of Jawa Tengah: Upstream Progo and Bogowonto watersheds. Unit hydrograph representing a watershed is obtained by averaging the results of unit hydrograph analysis on several flood cases occurs in the studied watershed, in which this study uses the unit hydrograph. Accuracy analysis of unit hydrograph is carried out by comparing design discharge resulted from used unit hydrograph application and referred design discharge reference, which is the discharge of used unit hydrograph result on the most flood cases and analysis result of measured maximum discharge frequency. Results of this study show a tendency that larger number of flood cases used to derive the unit hydrograph implies smaller peak of the resulted unit hydrograph and more accurate designed discharge calculation. To obtain less than 10% relative error on the designed discharge for the outmost numbers of flood cases, it requires at least 10 flood cases with spesific discharge between 0.40 to 1.10 m3/s/km2. Designed discharge resulted from unit hydrograph indicates over estimated as well as under estimated tendency for various period to maximum discharge of the frequency analysis with relatively short length of data (<10 years).